Os poderes instrutórios do juiz na perspectiva dos direitos fundamentais - Müller, Luciano Scherer (2012)
The purpose of this study is to situate the problem of the judge s fact-finding powers in the realm of the Constitutional and particularly of such powers from the standpoint of the Fundamental Right to a Fair Proceeding. Therefore, we seek to understand that the civil proceeding branded by the Constitutional State characters calls for active work by both the judge and the parties, given that the Fundamental Rights protect the citizens right to a fair proceeding carried out against one other and aiming at a fair decision. In that regard, after analyzing the insertion of civil proceedings in the Constitutional State culture and in the methodological phases completed while such proceedings are underway, and also after analyzing the fundamental rights, we are going to look into the fair proceeding, firmly understood here as a prerequisite for a fair decision. This study is also meant to examine the problem of truth as a requirement for a fair decision and its relation to the evidence and its guidelines in the current civil proceeding. As a result of this constitutional model imbued with the Fundamental Right to a Fair Proceeding, we are going to investigate the topic related to splitting the work to be done by the parties and the judge as a way to organize such fair proceeding, given that contemporary civil proceedings need to ensure the contending parties and society are provided with, by means of the judge s active participation in the case, social peace achieved in a fair, collaborative manner. From that standpoint, collaboration and the duties thereof present themselves as essential factors in the pursuit of fair proceedings, and are thus seen and presented in this study.